(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The objective of this study is to determine the nature of information-seeking behavior among student in Faculty of Film, Theatre, and Animation and to understand the way they search information to fulfill their information needs. The qualitative approach had served in this research. [14] model had been used in constructing the interview question. An interview session was conducted with nine (9) students. The triangulation data collection technique was employed in this case study. The findings of this study are that most participants’ had mentioned that they seek for information independently from the internet and friends. Due to that, they had spent much time in seeking information in order to represent it accurately. The limitation of this study is the participants and time constrain. This research only covers undergraduate students from the Faculty of Arts, Film and Theatre which only represent a small part of the arts community. Additionally, the researcher also had difficulties in making an appointment with them as most of their time had been allocated for attending class and had outdoors activity.